Cyanoacrylate Associated Foreign Body Granulomatous Gastritis: A Report of Three Cases. (19th January 2017) - Guner, Gunes; Kurtulan, Olcay; Kav, Taylan; Sokmensuer, Cenk; Gedikoglu, Gokhan; Akyol, Aytekin
Abstract : Granulomas are rarely seen in gastric biopsies mostly as an involvement of granulomatous diseases like sarcoidosis, Crohn's disease, infections, neoplasms, and vasculitis. Here, we claim cyanoacrylate as a foreign body type granuloma-causing agent in the stomach after vascular embolisation. We present cyanoacrylate associated gastric changes of three cases: two endoscopic biopsies and one gastric resection. In two cases, cyanoacrylate associated ulcers and granulomatous inflammation were observed in gastric mucosal biopsies following endoscopic examination after 7 months and 6 years of the glue injections, respectively. In the third case, the cyanoacrylate injection was performed 2 months prior to the surgery. Then the patient underwent distal pancreatectomy for pancreatic adenocarcinoma and during the operation a gastric mass was resected with a suspicion of tumoral infiltration. These three cases demonstrated that glue exposure causes active chronic inflammation with foreign body type granulomas, mucosal ulceration, and bleeding in the gastric mucosa. Even further, it can induce mass formation in the injection sites.